1996
DOI: 10.1002/cber.19961290116
|View full text |Cite
|
Sign up to set email alerts
|

Coordination Chemistry of Dimethylgold Halides with Bidentate Phosphorus and Arsenic Ligands – Revisited

Abstract: Dimethylgold(II1) chloride and bromide, (MezAuX)2, react with bis(diphenylphosphany1)methane (dppm, molar ratio 1 :2) to give the P-monohapto complexes cis-Me,AuX(dppm) (la, b) in quantitative yields. The products are readily oxidized by air to yield the P-hapto P'-monoxides 2a, b. Treatment of la, b with AgN03 affords an ionic nitrate [MezAu(dppm) complexes arose from the discovery that these compounds are surprisingly stable both thermally (e.g. as compared to silver compounds!), and also towards water and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 27 publications
3
17
0
Order By: Relevance
“…The findings confirm previous observations that gold(I) salts catalyze the oxidation of tertiary phosphines to the corresponding phosphine oxides [24]. It is also again obvious [30] …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The findings confirm previous observations that gold(I) salts catalyze the oxidation of tertiary phosphines to the corresponding phosphine oxides [24]. It is also again obvious [30] …”
Section: Discussionsupporting
confidence: 90%
“…However, there is precedent for this phenomenon: 1 : 1 complexes of gold(I) or gold(III) with ditertiary phosphines R 2 P(CH 2 ) n PR 2 are readily converted to complexes of the monoxides R 2 P(CH 2 ) n PR 2 O even with traces of oxygen [24]. As another parallel, the tertiary phosphine ligands R 3 P in the copper(I) cluster complex (R 3 P) 4 [Cu 4 OCl 6 ] were found to be readily oxidized even by traces of oxygen to give the cluster complex (R 3 PO) 4 [Cu 4 OCl 6 ] [7].…”
Section: Preparationmentioning
confidence: 99%
“…The structure of [Au 3 Cl 2 (dppm) 2 ]PF 6 is based on a triangular Au 3 -core (Figure 2.46d) [260]. Reaction of [AuBr(CH 3 ) 2 (dppm)] with AgNO 3 in methanol affords the tetranuclear species shown in Figure 2.46e [261]. Longer chains afford different features and thus the crystal structures shown by compounds of empirical formula [Au{PPh 2 (CH 2 ) n PPh 2 }] þ consist on rings [Au 2 {PPh 2 (CH 2 ) n PPh 2 } 2 ] 2þ for n ¼ 3 or 5 but a polymer for n ¼ 4 [262].…”
Section: Complexes With Bridging Bidentate Ligandsmentioning
confidence: 99%
“…A search of the Cambridge Structural Database (Version of October 1998; Allen & Kennard, 1993) indeed revealed that the longest Au III ÐP bonds are formed trans to '-carbon ligands: e.g. cis-[Au(CH 3 ) 2 (PPh 3 )(OPh)] 2.402 (4) A Ê (Sone et al, 1991); cis-[Au(CH 3 ) 2 {Ph 2 P(O)CH 2 PPh 2 }Cl] 2.389 (2) A Ê (Paul & Schmidbaur, 1996); [Au(2-PhNNC 6 H 4 ){3,4,5-(CH 3 O) 3 -C 6 H 2 -COCH 2 }(PPh 3 )Cl] 2.386 and 2.390 (2) A Ê (Vicente et al, 1993). Typical examples without such ligands are [Au(C 6 F 5 )(S 2 -C 6 H 4 )PPh 3 ] 2.340 (1) A Ê (Cerrada et al, 1995); [AuCl 3 (PPh 3 )] 2.335 (4) A Ê (Bandoli et al, 1973); [AuMe 3 (PPh 3 )] 2.350 (6) and 2.347 (6) A Ê (Stein et al, 1981); [Au(SC 6 H 4 PPh 2 ) 2 ]BPh 4 2.325 (4) and 2.332 (4) A Ê (Dilworth et al, 1994).…”
Section: Commentmentioning
confidence: 99%